Depression, anxiety, insomnia and interleukins in the early postpartum period - Drozdowicz-Jastrzębska, Ewa; Mach, Anna; Skalski, Michał; Januszko, Piotr; Jabiry-Zieniewicz, Zoulikha; Siwek, Marcin; Wawrzyniak, Zbigniew Maciej; Radziwoń-Zaleska, Maria (Frontiers in Psychiatry, 2023)
Background: Some new mothers have been shown to suffer from anxiety and depression associated with insomnia during the postpartum period. Our study assessed the impact of demographic, psychopathological, and biochemical factors on the incidence of depression in women during the early postpartum period.Methods: A total of 119 women were evaluated at 24-48 hours postpartum with the following psychometric scales: Hamilton Depression Rating Scale (HDRS), Edinburgh Postnatal Depression Scale (EPDS), Hailton Anxiety Rating Scale (HARS) and Athens Insomnia Scale (AIS). In addition, blood was drawn to assay interleukin 6 (IL-6) and interleukin 10 (IL-10).Results: The factors that had the greatest impact on the risk of postpartum depression detected with the HDRS were high HARS scores and evidence of insomnia in the AIS. There were no significant differences in IL-6 or IL-10 levels in women with and without depression (based on either HDRS or EPDS scores) and insomnia (based on AIS) after childbirth. Considering demographic factors, divorced and single women were shown to be at higher risk of postpartum depression (based on EPDS scores).Limitations: Small sample size and short observation span.Conclusions: This study highlights the relationship between postpartum depression and both anxiety and insomnia and emphasises the importance to assess symptoms of anxiety and sleep quality as part of screening in women at risk of postpartum depression.